2014
DOI: 10.1152/ajpregu.00519.2013
|View full text |Cite
|
Sign up to set email alerts
|

Phase-dependent resetting of the adrenal clock by ACTH in vitro

Abstract: Yoder JM, Brandeland M, Engeland WC. Phase-dependent resetting of the adrenal clock by ACTH in vitro. Am J Physiol Regul Integr Comp Physiol 306: R387-R393, 2014. First published January 29, 2014 doi:10.1152/ajpregu.00519.2013The adrenal cortex has a molecular clock that generates circadian rhythms in glucocorticoids, yet how the clock is synchronized to the external environment is unknown. Using mPER2::Luciferase (mPER2Luc) knockin mice, in which luciferase is rhythmically expressed under the control of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 53 publications
2
26
0
Order By: Relevance
“…We have shown that the adrenal clock is phase shifted by ACTH in vitro and that the phase shift is phase dependent (47). However, our in vitro experiments showed that ACTH produced a phase delay in the adrenal PER2Luc rhythm when administered at a circadian time analogous to the active phase of the rhythm, but no phase advance at the circadian time representing the inactive phase.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…We have shown that the adrenal clock is phase shifted by ACTH in vitro and that the phase shift is phase dependent (47). However, our in vitro experiments showed that ACTH produced a phase delay in the adrenal PER2Luc rhythm when administered at a circadian time analogous to the active phase of the rhythm, but no phase advance at the circadian time representing the inactive phase.…”
Section: Discussionmentioning
confidence: 58%
“…Adrenals and anterior pituitaries were rapidly excised and placed in cold Hank's Balanced Salt Solution. Cleaned and hemisected adrenals or whole pituitaries were cultured on Millicell organotypic inserts in a 35-mm Petri dish with 1.5 ml of warmed culture media (Dulbecco's Modified Eagle Media without phenol red) supplemented with luciferin and penicillinstreptomycin as described previously (47,48). Dishes were sealed with circular glass coverslips and silicon grease.…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral tissues (adrenal gland, cornea, lung, liver, spleen and anterior pituitary) were rapidly dissected and placed in ice-cold Hank's solution. Each tissue explant was placed on a membrane (0.4μm, 30 mm in diameter, Millicell cell culture inserts; Millipore, Billerica, MA, USA) in a 35 mm Petri dish, sealed with vacuum grease, and cultured in 1.1 ml DMEM containing 10 mM HEPES, 0.1 mM Luciferin (Promega, Madison, WI), 25 units/ml penicillin, 25 μg/ml streptomycin (Gibco, Grand island, NY), and 2% B27 (Gibco) as described previously [19]. Cultures were incubated at 37°C, and bioluminescence was monitored for 1 min at 7.5-min intervals using a LumiCycle luminometer (Actimetrics, Evanston, IL).…”
Section: Methodsmentioning
confidence: 99%
“…The light pulse data discussed above suggest that adrenal clocks are entrained by neuronal mechanisms (Buijs et al 1999, Ishida et al 2005. However, Yoder and coworkers recently found that ACTH itself can also shift the phase of the adrenal Per2 rhythm (Yoder et al 2014). One might speculate that, in this way, stress-induced HPA axis activation can reset adrenal clocks, thus affecting circadian GC release.…”
Section: Circadian Regulation Of the Hpa Axismentioning
confidence: 97%